Protective association of milk intake on the risk of hip fracture: Results from the Framingham Original Cohort - Sahni, Shivani (J Bone Miner Res, 2014)
Dairy foods are rich in bone beneficial nutrients, yet the role of dairy foods in hip fracture prevention remains controversial. The objective was to evaluate the association of milk, yogurt, cheese, cream and milk+yogurt intakes with incident hip fracture. 830 men and women from the Framingham Original Cohort, a prospective cohort study, completed a food frequency questionnaire (1988–89) and were followed for hip fracture until 2008. In this population-based study, Cox-proportional hazards regression was used to estimate Hazard Ratios (HR) by categories of energy-adjusted dairy intake (servings/week) adjusting for standard confounders. The exposure was energy adjusted intakes of milk, yogurt, cheese, cream and milk+yogurt (servings/wk). Risk of hip fracture over the follow-up was the primary outcome; the hypothesis being tested was formulated after data collection. The mean age at baseline was 77y (SD:4.9, range: 68–96). 97 hip fractures occurred over the mean follow-up time of 11.6y (range: 0.04–21.9y). The mean±SD (servings/wk) of dairy intakes at baseline were: milk=6.0±6.4, yogurt=0.4±1.3, cheese=2.6±3.1; cream=3.4±5.5. Participants with medium (>1 and <7serv/wk) or higher (≥7serv/wk) milk intake tended to have lower hip fracture risk than those with low (≤1serv/wk) intake [HR(95%CI): high vs low intake: 0.58 (0.31–1.06), P=0.078; medium vs. low intake: 0.61 (0.36–1.08), P=0.071; P trend: 0.178]. There appeared to be a threshold for milk, with 40% lower risk of hip fracture among those with medium/high milk intake, compared to those with low intake (P=0.061). A similar threshold was observed for milk+yogurt intake (P=0.104). These associations were further attenuated after adjustment for femoral neck bone mineral density. No significant associations were seen for other dairy foods (P range, 0.117–0.746). These results suggest that greater intakes of milk and milk+yogurt may lower risk for hip fracture in older adults through mechanisms that are partially, but not entirely, due to effects on bone mineral density.